Losses from simulated defaults in Canada's large value transfer system - Nellie Zhang; Tom Hossfeld (Bank of Canada, 2010)
The Large Value Transfer System (LVTS) loss-sharing mechanism was designed to ensure that, in the event of a one-participant default, the collateral pledged by direct members of the system would be sufficient to cover the largest possible net debit position of a defaulting participant. However, the situation may not hold if the indirect effects of the defaults are taken into consideration, or if two participants default during the same payment cycle. The authors examine surviving participant total losses under both one clearungand two-participant default conditions, assuming the potential knock-on effects of the default. Their analysis includes the impact of a decline in value of LVTS collateral following an unexpected default. Simulations of participant defaults indicate that the impact on the LVTS is generally small; surviving participants do incur end-of-day collateral shortfalls, but only rarely and in small amounts. Under the two-participant default scenario, the likelihood of the Bank of Canada having to provide funds to ensure LVTS settlement is reasonably low, as is the average residual-coverage amount. The majority of LVTS participants pledge as collateral securities issued by other system members. However, the impact of an issuer of such collateral defaulting is generally not significant in the LVTS.
Keywords: E47; G21; 330; Financial stability; Payment; clearing; and settlement systems; Financial institutions; Finanzmarkt; Bank; Bankenkrise; Verrechnungsverkehr; Kreditsicherung; Kanada